2013
DOI: 10.1089/ars.2012.4797
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotection After Stroke by Targeting NOX4 As a Source of Oxidative Stress

Abstract: Significance: Stroke, a leading cause of death and disability, poses a substantial burden for patients, relatives, and our healthcare systems. Only one drug is approved for treating stroke, and more than 30 contraindications exclude its use in 90% of all patients. Thus, new treatments are urgently needed. In this review, we discuss oxidative stress as a pathomechanism of poststroke neurodegeneration and the inhibition of its source, type 4 nicotinamide adenine dinucleotide phosphate (NADPH) oxidase (NOX4), as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
109
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(111 citation statements)
references
References 72 publications
2
109
0
Order By: Relevance
“…It brings irreversible injury of brain tissue if the cerebral blood vessel cannot be recanalized timely. Clinically, quick thrombolysis to restore blood flow as early as possible is recommended for the treatment of ischemic stroke [3]. The only proven thrombolytic therapy for acute ischemic stroke was achieved by intravenous use of t-PA.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It brings irreversible injury of brain tissue if the cerebral blood vessel cannot be recanalized timely. Clinically, quick thrombolysis to restore blood flow as early as possible is recommended for the treatment of ischemic stroke [3]. The only proven thrombolytic therapy for acute ischemic stroke was achieved by intravenous use of t-PA.…”
Section: Discussionmentioning
confidence: 99%
“…It is one of the leading causes of death and disability worldwide. However, few therapeutic methods or drugs have adequate effects in the clinical treatment of ischemic stroke [2,3]. Timely recanalization of cerebral artery vessels and reintroduction of blood flow allow ischemic stroke-induced impairments to be arrested and reversed, thus, it is considered as an efficient therapy [3].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…(86)] or NOX4 [comprehensively reviewed in ref. (137)] isoforms are the key pharmacological target for stroke. Interestingly, a recent report showed that deletion of the proton channel Hv1 significantly protected from brain damage caused by ischemic stroke (186).…”
Section: Nox/ros and Neurovascular Diseasementioning
confidence: 99%